The importance of escape clauses: Firm response to thin capitalization rules - Martin Eckhoff Andresen; Lars Thorvaldsen (Statistics Norway, Research Department, 2023)
Escape clauses, where small firms are exempt from particular tax rules, is a crucial feature of a number of corporate tax schemes, but creates incentives to avoid taxation by manipulating the measures that determine inclusion. We evaluate the impact of thin capitalization rules, which commonly feature such escape clauses, by exploiting the introduction of these rules in Norway in 2014. Combining difference-indifferences, regression discontinuity and bunching estimates, we show that what appears to be a strong response in the capital structure among exposed firms primarily reflect within-group reallocation of debt to avoid exposure to the rules through escape clauses. We observe sharp bunching among both new and existing subsidiaries at both thresholds for rule inclusion, and find that internal corporate group debt is offloaded to these bunching subsidiaries in order to avoid additional tax costs. As a result, significant and large effects on firm-level capital structure in response to the thin capitalization rules is driven by reshuffling of capital within corporate groups with little real effects. Re-estimating the difference-indifference specification at the corporate group level confirms this finding, questioning the extent to which thin capitalization rules have the intended effect due to the presence of escape clauses.
Keywords: H25; H26; G30; 330; Thin capitalization rules; capital structure; escape clauses; difference-in-differences; bunching